2021
DOI: 10.14742/ajet.6617
|View full text |Cite
|
Sign up to set email alerts
|

Review of smart learning: Patterns and trends in research and practice

Abstract: This article presents a review of the literature on smart learning in order to provide a comprehensive overview of its latest developments in research and practice. The review covered 90 studies published from 2010 to 2019, which were collected from three publication databases, namely Web of Science, Scopus and ProQuest. They were analysed for the patterns and trends in terms of publication years, sources of publication, countries or regions of publication, research purposes, research methods, educational leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 41 publications
(64 reference statements)
0
7
0
2
Order By: Relevance
“…11 Li & Wong (2021) Integration of smart learning with advanced technologies to facilitate student learning and interaction…”
Section: Higher Education Institutionmentioning
confidence: 99%
“…11 Li & Wong (2021) Integration of smart learning with advanced technologies to facilitate student learning and interaction…”
Section: Higher Education Institutionmentioning
confidence: 99%
“…At the same time, schools should provide technical support for students in terms of using hardware and software, such as making operation guidelines freely and easily available, establishing information technology service platforms with professional staff dedicated to providing technical services, so that students can concentrate on learning rather than solving technical issues (Zhan et al, 2021). In addition, it is also highly desirable that smart classroom learning environments fulfill the requirements of learners with differential competencies, learning styles and interests (Gros, 2016;Li & Wong, 2021). Thus, instructors and school administrators should equip classrooms with various ICT devices in an attempt to cater to students' varying levels of information literacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these efforts, evidence has shown that the effects of smart classrooms on promoting students' learning, through advanced ICT and improving academic performance, have not met the latter expectations (Mao et al, 2018). In particular, researchers have criticised the fact that smart classroom learning environments invest large amounts of money in order to construct the most advanced facilities, without considering student perspectives (K. Li et al, 2016;K. C. Li & Wong, 2021;Ze & Fu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of educational technology has made the smart classroom more social, interactive, flexible, and a student-centered learning environment ( Kaufmann and Vallade, 2020 ; Li and Wong, 2021 ). Given their advantages, many countries have invested significantly in smart classrooms to promote students’ learning ( Temdee, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%